14 + 6p = 6 + 7p 8 = p
8p+5 = 11+7p= 8p-7p = 11-5p = 6
7p + 2 = 5p + 8 7p - 5p = 8 - 2 2p = 6 p = 3
-7p + 5r - 6p + 3r = -7p - 6p + 5r + 3r = -(7 + 6)p + (5 + 3)r = -13p + 8r
4p + 6 = 2 4p = -4 (subtracting 6 from both sides) p = -1 (dividing both sides by 4)
15 + 3 = 7p - 4p ie 18 = 3p so p = 6
14 + 6p = 6 + 7p 8 = p
8p+5 = 11+7p= 8p-7p = 11-5p = 6
7p + 2 = 5p + 8 7p - 5p = 8 - 2 2p = 6 p = 3
-7p + 5r - 6p + 3r = -7p - 6p + 5r + 3r = -(7 + 6)p + (5 + 3)r = -13p + 8r
4p + 6 = 2 4p = -4 (subtracting 6 from both sides) p = -1 (dividing both sides by 4)
6
6
The expression can be simplified to: -8p--29
-39 + 6 = -33
2x + 6 + 9x = 39 11x + 6 = 39 11x = 39 - 6 11x = 33 x = 3
3p + 6 = 4p + 6 This implies that, 3p - 4p = 6 - 6 -1p = 0 Therefore, p = 0/-1 = 0